Peningkatan Pemahaman Mengenai Kewajiban Menutup Aurat Bagi Wanita Melalui Bimbingan Kelompok Berbasis Al-Qur’an pada Mahasiswa - Jannati, Zhila; Randicha Hamandia, Muhammad (Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2024)
Covering a woman's private parts is proof that she loves Allah SWR. and obey the commands of Allah SWT. She is a woman who longs for heaven as an eternal residence in the future. The aim of this research is to find out how to increase understanding regarding the obligation to cover the private parts for women through group guidance based on the Koran for students of the Islamic Guidance and Counseling study program, Faculty of Da'wah and Communication, UIN Raden Fatah Palembang. The approach in this research is a qualitative approach with descriptive methods. The research subjects were 10 students of Islamic Guidance and Counseling, Faculty of Da'wah and Communication, UIN Raden Fatah Palembang. The data collection techniques use observation, interviews and documentation. Meanwhile, data analysis uses qualitative descriptive data analysis. This research obtained results namely that group guidance based on the Koran was implemented through four stages, namely the formation stage, transition stage, activity stage and termination stage. Then, understanding of the obligation to cover the private parts of students has increased, namely understanding of the meaning of private parts, the limits of private parts for women, the law on covering private parts, as well as threats for women who do not want to cover private parts.